Planning, shortage and transformation essays in honour of Janes Kornai - Kornai, Janos; Maskin, Eric (Ed.); Simonovits, Andrais (Ed.) (Cambridge MIT Press, 2000)
The book`s title,`Planning,Shortage and Transformation` reflects three of the major themes in Jano`s work.The volume is divided into three parts with a philosophical introduction with central question :How do socioeconomic systems work?More specifically
Keywords: Economic policy; Scarcity; Post-Communism; Europe, Eastern-Economic policy